1999
DOI: 10.1116/1.591045
|View full text |Cite
|
Sign up to set email alerts
|

Formation of low resistance Pt ohmic contacts to p-type GaN using two-step surface treatment

Abstract: Two-step surface treatment is introduced to obtain low resistance Pt contacts to p-type GaN. The first step is performed after the mesa etching process using buffered oxide etch ͑BOE͒ and ammonium sulfide ͓(NH 4 ͒ 2 S x ͔. This is followed by the second step using BOE. The Pt contact, that was simply BOE treated, yields 2.1(Ϯ0.9)ϫ10 Ϫ2 ⍀ cm 2. However, the contact which was treated sequentially using ultrasonically boiled BOE ͑10 min͒ and boiled (NH 4 ͒ 2 S x ͑10 min͒, produces a specific contact resistance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
75
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 13 publications
1
75
0
Order By: Relevance
“…This is further complicated by the fact that oxide reaily forms at the GaN surface [2]. Currently, lowering of contact resistivity is commonly achieved by reducing oxide and contamination at the surface with various cleaning recipes, the most effective of which reported is the use of boiling aqua regia [3] or (NH 4 ) 2 S x [4].…”
Section: Introductionmentioning
confidence: 98%
“…This is further complicated by the fact that oxide reaily forms at the GaN surface [2]. Currently, lowering of contact resistivity is commonly achieved by reducing oxide and contamination at the surface with various cleaning recipes, the most effective of which reported is the use of boiling aqua regia [3] or (NH 4 ) 2 S x [4].…”
Section: Introductionmentioning
confidence: 98%
“…In fact, the high contact resistance of GaN is one of major obstacles to the realisation of long-lifetime operation of GaN-based optical devices. Thus, to develop high-quality Ohmic contacts, different surface treatments using KOH [2], HNO 3 : HCl [3], buffered oxide etch (BOE) [4,5], (NH 4 ) 2 S x [6], and Na 2 S [7] solutions have been employed. Kim et al [3] showed that for Pd/Au Ohmic contacts to p-GaN, the surface treatment with HNO 3 : HCl leads to a specific contact resistance of $10 --4 W cm 2 .…”
mentioning
confidence: 99%
“…However, it is difficult to obtain p-type Ohmic contacts with low specific contact resistance (q c ) of less than 10 --4 W cm 2 to p-type GaN, because its hole concentration is less than 10 18 cm --3 due to the relatively deep acceptor level of Mg atoms in p-type GaN. To date, there have been various attempts to reduce the contact resistance by surface treatment [1,2] or metal deposition and annealing [3][4][5][6]. These methods have a strong effect in reducing the q c values to the 10 --4 W cm 2 range or less.…”
mentioning
confidence: 99%